Strong Ties in a Small World - Marco van der Leij; Sanjeev Goyal (Tinbergen Institute, 2006)
In this paper we test the celebrated `Strength of weak ties' theory of Granovetter (1973). We test two hypotheses on the network structure in a data set of collaborating economists. While we find support for the hypothesis of transitivity of strong ties, we reject the hypothesis that weak ties reduce distance more than strong ties do. We relate this surprising result to two different views of society. Whereas the classical view has been that society consists of different communities with strong ties within communities and weak ties between, the community of economic researchers has an interlinked star structure with strong ties between the stars. In such a world, strong ties are more important than weak ties.
Keywords: A14; Z13; 330; network structure; social network; social capital; economic sociology; coauthorship; research; collaboration